1995
DOI: 10.1007/bf01447666
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and emotional problems among Chinese and American children: Parent and teacher reports for ages 6 to 13

Abstract: This study compared behavioral and emotional problems reported by parents and teachers in Chinese urban and rural samples and demographically similar American samples. Parents of 469 6-to-13-year-old children of each nationality completed the Child Behavior Checklist (CBCL). Teachers completed the Teacher's Report Form (TRF). Cross-cultural differences were generally modest in magnitude. Chinese children scored higher on TRF Delinquent Behavior and Anxious/Depressed syndromes, and on Internalizing. American ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 27 publications
10
52
0
1
Order By: Relevance
“…Chinese girls are higher than Chinese boys in internalizing problems in childhood and adolescence, whereas Chinese boys are higher in externalizing problems (Liu et al, 2001;Weine et al, 1995). Consistent with the idea that depressed children and adolescents are unregulated, Chan (1994) found that youth with anxiety and depression tended to use ineffective rather than rational problem-solving modes of coping.…”
Section: The Role Of Culturementioning
confidence: 94%
See 1 more Smart Citation
“…Chinese girls are higher than Chinese boys in internalizing problems in childhood and adolescence, whereas Chinese boys are higher in externalizing problems (Liu et al, 2001;Weine et al, 1995). Consistent with the idea that depressed children and adolescents are unregulated, Chan (1994) found that youth with anxiety and depression tended to use ineffective rather than rational problem-solving modes of coping.…”
Section: The Role Of Culturementioning
confidence: 94%
“…Studies suggest that rates of depression and internalizing problems in China and Hong Kong are at least as high as in the United States (e.g., Chen & Li, 2000;Greenberger, Chen, Tally, & Dong, 2000;Liu et al, 1999Liu et al, , 2000Stewart et al, 2004), and that U.S. children are higher in aggressive behavior (Weine, Phillips, & Achenbach, 1995). Chinese girls are higher than Chinese boys in internalizing problems in childhood and adolescence, whereas Chinese boys are higher in externalizing problems (Liu et al, 2001;Weine et al, 1995).…”
Section: The Role Of Culturementioning
confidence: 99%
“…It is interesting tu note, however, that the mean level of parental monitoring did not differ significantly among the three groups. Although it is not clear why Feldman et al found significant differences in mean level of misconduct between Chinese and Americans, whereas Weine et al ( 1995) did not, these two studies differed with respect to several sample characteristics. Among the differences were age group (high school students vs. elementary school students) , residence ( Hong Kong vs. Mainland China), a nd source of information (adolescents' self-report vs. teachers' and parents' reports) .…”
mentioning
confidence: 86%
“…The risks of dysfunctional behaviors and low adaptability in children and adolescents with syncope were assessed using the standardized Italian version of the Youth SelfReport form for patients 11-18 years (YSR/11-18) [10,11]. It is a selfreport questionnaire with eight syndrome subscales (Anxious/ Depressed, Withdrawn/Depressed, Somatic Complaints, Social Problems, Thought Problems, Attention Problems, Rule-Breaking Behavior, and Aggressive Behavior) which are related to screening emotional and behavioral problems across multiple cultures [12,13]. Although no normative Italian data on the most recent YSR are available to date, the psychometric properties of the previous YSR [14] version have been investigated recently in a study conducted in Italy, that showed the good validity and reliability of this test on the Italian population [15].…”
Section: Psychological Assessmentmentioning
confidence: 99%